Fan Labor As A Shield Against Platforms’ Unsafety: The Pipoca & Nanquim Case - Costa, Thiago; Blanco, Beatriz (AoIR Selected Papers of Internet Research, 2026)
Digital platforms’ governance model for cultural production is based on making content creators entirely responsible for producing, publishing and moderating their work. This arrangement makes digital influencers especially vulnerable to harassment, overworking, and arbitrary politics regarding content management and unfair censure. Since content creators are on their own, they have been deploying multiple strategic approaches to keep themselves and their content safe despite platforms’ lack of assistance. Many of them involve camaraderie, such as self-organized groups focused on information exchange and mutual support, and often they mobilize their fanbase to deal with safety issues, such as harassment, asking the fans to mass report aggressors to make their claim more relevant to platforms through engagement. We draw on a case study of the deletion and recovery of Pipoca & Nanquim YouTube channel to contextualize how Brazilian content creators learned to mobilize their fan bases to manage their vulnerability on social media platforms. Through a combination of case study methodology and narrative interviews with the Pipoca & Nanquim team, we propose an analysis of how fan labor is central for Brazilian content creators in regards to safety and acknowledgment by platforms’ administration. And, since digital influencers must rely only on their engagement to protect themselves, we also question how this context affects people from social minority groups who work as digital influencers in Brazil, reinforcing oppressive structures despite the DEI discourse often adopted by digital platforms representatives.